Umbilical port versus epigastric port for gallbladder retrieval in laparoscopic cholecystectomy: An intervention study - Shakil Jawed; Shaikh Md Nafis Jahangir; Imdadul Haque (Asian Journal of Medical Sciences, 2024)
Background: Open cholecystectomy as a routine operation once for cholecystitis and cholelithiasis is no more a routine practice. Laparoscopic cholecystectomy (LC) is one of the most common surgeries done these days and has become the gold standard for the treatment of symptomatic cholelithiasis. Aims and Objectives: The aim of the study was to compare the retrieval of gallbladder (GB) between epigastric port and umbilical port as two approaches of LC in terms of the time taken to remove GB, pain, and other complications postoperatively. Materials and Methods: An intervention study was conducted in the general surgery department between June 2022 and May 2023 among 73 patients who were admitted for cholecystectomy recruited by a total consecutive sampling method. Patients were put into two modalities of retrieval of GB by performing the two methods alternately. Templates were generated in MS Excel sheet and analysis was done. Appropriate statistical tests were used and the P<0.05 was taken as significant. Results: There was no significant difference in the mean age (P=0.21) of patients as well as the mean duration of surgery (P=0.07) through epigastric port as compared to umbilical port. Patients who had undergone retrieval of GB through epigastric port (P=0.04) had significantly lesser pain at 6 h post-operation as compared to epigastric port. The overall pain scores were lesser when extraction of GB was done through epigastric port in comparison with umbilical port. The post-operative complications in terms of infection, hernia was lesser in patients undergoing extraction of GB through epigastric port. Conclusion: Epigastric port could be better as compared to umbilical port for retrieval of GB with respect to mean duration, post-operative pain and herniation from port site, and also surgical site infection.